Diplomacy in Western Asia in the Early Second Millennium В. С. - Munn-Rankin, J. M.
The Historical Background of the Mari Archive — The Concept of Divine Rule — Independent and Dependent States — Treaties — Arbitration and Mediation — Exchange of Letters and Gifts — Foreign Missions — Conclusion.